Экспериментальное исследование стабильности выходных характеристик Эталона РЭМП - Кравченко, Владимир Иванович; Немченко, Юрий Семенович; Танцура, Александр Иванович; Гирка, Юлия Николаевна (НТУ "ХПИ", 2007)
В статті розглядаються фактори, які можуть мати вплив на вихідні характеристики Еталона РЕМП. Експериментально досліджений ступінь їх впливу на амплітудно-часові параметри Еталона РЕМП. Зроблені висновки та запропоновані шляхи зменшення їх впливу.

In this article, factors which can influence output characteristics of primary REMP-standard are considered. The extent of their influence on amplitude and time parameters of primary REMP-standard was experimentally investigated. Conclusions are made, the ways of decreasing of their influence are proposed.
Keywords: амплитудно-временные параметры; импульсы; постоянное зарядное напряжение; электрическое поле; механические коммутаторы